Small boat - Delecroix, Vincent, 1969- (Mariner Books, 2026)
"In November 2021, an inflatable dinghy carrying migrants from France to the UK capsized in the English Channel, causing the deaths of 27 people on board. Despite receiving numerous calls for help, the French authorities wrongly told the migrants they were in British waters and had to call the British authorities for help. By the time rescue vessels arrived on the scene, nearly three hours later, all but two of the migrants had died, the worst single loss of life ever to occur in the Channel. Vincent Delecroix's acclaimed Small Boat is a fictional first-person account of the French radio operator who took the migrants' calls and her attempts to justify the indefensible. Accused of failing in her duty, she refuses to be held more responsible than others for this disaster than the crises behind these tragedies."--Publisher descripion.